Transparent solar cell using spin coating and screen printing - Suhayla, Alaa A. F. Husain; Wan Hasan, Wan Zuha (Universiti Putra Malaysia Press, 2017)
The development of Transparent Solar Cells (TSC) has become the main focus of solar energy research in recent years. The TSC has a number of applications and make use of unexploited space such as skyscraper windows. In this paper, TSC is fabricated using commercially available titanium dioxide (TiO2) P25 to make a paste, which is deposited on FTO glass using screen printing and spin coating methods. The effects of the thickness of the TiO2 film on transparency are examined. The paste is synthesised in the Cleanroom and used in both methods of deposition. The final cell fabrication is a Dye sensitised solar cell (DSSC). The obtained transparency of the FTO glass is 83%, and after the deposition of TiO2 it is reduced to less than 80%. The overall transparency of the DSSC, which was made using the spin coating method, is 70% with an Isc of 9.5 mA and Voc 853mV.